Yahoo Web Search

  1. Sort by

  1. π(r+6) ² = 15(2πr) + 2 πr² First, recognize that since everything on both... out of the equation entirely. π(r+6) ² = 15(2πr) + 2 πr² π(r+6) ² = π[15(2r) + 2r²] (r+6...

    5 Answers · Education & Reference · 20/09/2010

  2. ✰Answer✰ r = (-3y - 2k)/(a - 1) ✐Derivation✐ 2k + ar = r - 3y Try different... is the better way to solve for r. ar = r - 3y - 2k ar - r = -3y - 2k Factor the left side. r(a - 1) = -3y - 2k r = (-3y - 2k)/(a...

    3 Answers · Science & Mathematics · 27/07/2012

  3. GL(n,R) is the group of nxn invertible matrices under matrix multiplication, and... with determinant 1. Now first we have to show that SL(2,R) is a subgroup of GL(2,R). Clearly the identity element...

    1 Answers · Science & Mathematics · 06/04/2012

  4. I use DVD+R but it depends on your DVD burner. Most older...1) The DVD-R (pronounced "DVD dash R") and -RW media formats are officially approved...

    5 Answers · Consumer Electronics · 26/12/2006

  5. (r^(2)-36)/((r+6)^(2)) The binomial can be factored using the difference...difference of squares formula is a^(2)-b^(2)=(a-b)(a+b). ((r-6)(r+6))/((r+6)^(2)) Reduce the expression by canceling out...

    5 Answers · Science & Mathematics · 06/03/2010

  6. Let R be a relation on R(all reals) given by x R y iff x.... To show R is an equivalence relation, then we must show that R is reflexive, symmetric, and transitive. Reflexive: We must show...

    1 Answers · Science & Mathematics · 22/03/2014

  7. r - 2s = 14 Solve for s: Subtract r off both sides: -2s = 14 - r Multiply both sides by -1 to avoid trouble later: 2s = r - 14 Divide by 2: s = (r - 14)/2

    5 Answers · Science & Mathematics · 21/09/2012

  8. The Japanese 'r' is a mix of what is called an alveolar flap and an alveolar...a trill). The alveolar flap is the same as a Spanish 'r' in the middle of a word. Imagine the Croatian 'r', but...

    3 Answers · Society & Culture · 25/06/2015

  9. r^2h)/(2πrh+2πr^2)<1/3 (πr^2)/(2πr+2πr^2)<1/3 (πr^2)/2πr(1+r)<1/3 r/2(1+r)<1/3 r<...

    2 Answers · Science & Mathematics · 24/08/2012

  10. (7r + 10)/r(r + 1)(r + 2) = A/r + B/(r + 1) + C/(r + 2) A(r + 1...(r + 1) = 7r + 10 r = 0 --> 2A = 10 --> A = 5 r = -1 --> -B = 3 --> B = -3 r = -2 --> 2C = -4...

    1 Answers · Science & Mathematics · 03/01/2013

  1. Try asking your question on Yahoo Answers